Cultural epidemiology of pandemic influenza in urban and rural Pune, India: a cross-sectional, mixed-methods study. Issue 12 (8th December 2014) - Sundaram, Neisha; Schaetti, Christian; Purohit, Vidula; Kudale, Abhay; Weiss, Mitchell G
Abstract : Objective: To identify and compare sociocultural features of pandemic influenza with reference to illness-related experience, meaning and behaviour in urban and rural areas of India. Design: Cross-sectional, mixed-methods, cultural epidemiological survey with vignette-based interviews. Semistructured explanatory model interviews were used to study community ideas of the 2009 influenza pandemic. In-depth interviews elaborated respondents' experience during the pandemic. Setting: Urban and rural communities, Pune district, western India. Participants: Survey of urban (n=215) and rural (n=221) residents aged between 18 and 65 years. In-depth interviews of respondents with a history of 2009 pandemic influenza (n=6). Results: More urban (36.7%) than rural respondents (16.3%, p<0.001) identified the illness in the vignette as 'swine flu'. Over half (56.7%) believed the illness would be fatal without treatment, but with treatment 96% predicted full recovery. Worry ('tension') about the illness was reported as more troubling than somatic symptoms. The most common perceived causes—'exposure to a dirty environment' and 'cough or sneeze of an infected person'–were more prominent in the urban group. Among rural respondents, climatic conditions, drinking contaminated water, tension and cultural ideas on humoral imbalance from heat-producing or cold-producing foods were more prominent. The most widely reported home treatment was herbal remedies; more rural respondents suggested reliance on prayer, and symptom relief was more of a priority for urban respondents. Government health services were preferred in the urban communities, and rural residents relied more than urban residents on private facilities. The important preventive measures emphasised were cleanliness, wholesome lifestyle and vaccines, and more urban respondents reported the use of masks. In-depth interviews indicated treatment delays during the 2009 pandemic, especially among rural patients. Conclusions: Although the term was well known, better recognition of pandemic influenza cases is needed, especially in rural areas. Improved awareness, access to treatment and timely referrals by private practitioners are also required to reduce treatment delays.